Epidemiology of the Use of Hemostatic Agents in Children Supported by Extracorporeal Membrane Oxygenation: A Pediatric Health Information System Database Study - Nellis, Marianne E.; Vasovic, Ljiljana V.; Goel, Ruchika; Karam, Oliver (Frontiers in Pediatrics, 2021)
ABSTRACT Objectives: Children supported by extracorporeal membrane oxygenation (ECMO) are at high risk of bleeding. Though practitioners often prescribe blood components and/or medications to prevent or treat bleeding, the utilization of these hemostatic measures in children is not well understood. We sought to evaluate the use of hemostatic blood products (platelet, plasma and cryoprecipitate transfusions) and medications (aminocaproic acid, tranexamic acid [TXA] and Factor VIIa) in children supported by ECMO. Design: Retrospective observational study using the Pediatric Health Information System (PHIS) database from 2011-2017. Setting: Fifty-one U.S. children’s hospitals Patients: Children (aged 0-18 years) supported by ECMO Interventions: None Measurements and Main Results: ECMO was employed in the care of 7910 children for a total of 56,079 ECMO days. Fifty-five percent of the patients were male with a median (IQR) age of 0 (0-2) years. The median (IQR) length of ECMO was 5 (2-9) days with a hospital mortality rate of 34%. Platelets were transfused on 49% of ECMO days, plasma on 33% of ECMO days and cryoprecipitate on 17% of ECMO days. Twenty-two percent of children received TXA with the majority receiving it on the first day of ECMO and the use of TXA increased during the six-year period studied (p<0.001). Seven percent of children received aminocaproic acid and 3% received Factor VIIa. Conclusions: Children supported by ECMO are exposed to a significant number of hemostatic blood products. Antifibrinolytics, in particular TXA, are being used more frequently. Given the known morbidity and mortality associated with hemostatic blood products, studies are warranted to evaluate the effectiveness of hemostatic strategies.